Neisseria lactamica Y92-1009 complete genome sequence. - Pandey, AK; Cleary, DW; Laver, JR; Maiden, MCJ; Didelot, X; Gorringe, A; Read, RC (BioMed Central, 2017)
We present the high quality, complete genome assembly of Neisseria lactamica Y92-1009 used to manufacture an outer membrane vesicle (OMV)-based vaccine, and a member of the Neisseria genus. The strain is available on request from the Public Health England Meningococcal Reference Unit. This Gram negative, dipplococcoid bacterium is an organism of worldwide clinical interest because human nasopharyngeal carriage is related inversely to the incidence of meningococcal disease, caused by Neisseria meningitidis. The organism sequenced was isolated during a school carriage survey in Northern Ireland in 1992 and has been the subject of a variety of laboratory and clinical studies. Four SMRT cells on a RSII machine by Pacific Biosystems were used to produce a complete, closed genome assembly. Sequence data were obtained for a total of 30,180,391 bases from 2621 reads and assembled using the HGAP algorithm. The assembly was corrected using short reads obtained from an Illumina HiSeq 2000instrument. This resulted in a 2,146,723 bp assembly with approximately 460 fold mean coverage depth and a GC ratio of 52.3%.